Legal Problems In Implementation Deed Of Murobahah Agreement Execution Mortgage At Bank Shariah Mandiri - Muhamad Imanullah; Yogi Setiyo Pamuji (Jurnal Akta, 2019)
Bank of Shariah as a new financial institution that emerged much later than conventional banks, in its operations will face various problems it is a challenge for Islamic banks.The purpose of this study was to determine the know: 1) the development of Islamic Agreement made in the form UUJN Deed in accordance with the terms of both form and substance; (2) The assurance certificate and the legal protection of the parties to the deed; (3) The obstacles in the execution of the security rights at Bank Shariah Mandiri.The method used is a problem with juridical sociological approach, specification using descriptive analytical research, collecting data from field studies and literature, technical data analysis with qualitative descriptive.The final conclusion is that: 1) In the Islamic banking, notary is authorized to make a warranty deed in Murabahah financing agreement, made in the form of the Deed of Acknowledgment of Debt with the Provision of Security and Authorization to Sell. Inside the deed in addition to providing power to sell the bank if the debtor defaults, the bank is also given the power to take care of the land certificate, if the certificate has been completed debtor authorizes the bank to install Deed Mortgage Encumbrances rights to the land. 2) Certainty Murobahah Deed and Legal protection against the parties in the government as the deed Murobahah is organizing institutions of governance, particularly the shade of a notary office is required to provide insight to improve contract-related notary Shariah in particular, through training contract manufacturing of Shariah, or seminars to improve Notary services to the community for the better and the maximum. 3) The resistance that occurs is the debtor convoluted in negotiations to resolve the security rights, the incompatibility of the price of the auction conducted by the debtor and the latter is the resistance efforts of the debtor law that pursue a lawsuit to the District Court.Keywords : Murobahah Agreement; Execution Mortgage; Bank Shariah Mandiri.